Different hydrocolloid types and concentrations effects towards non-gluten sponge cake's chemical quality and organoleptic - Ayu Lestari Doloksaribu; Fadjar Kurnia Hartati (Universitas Dr Soetomo, 2021)
The number of people with autism and celiac disease keeps increasing. One of the efforts to assist the healing process naturally is through food consumption that is healthy, safe, and not carelessly, such as providing non-gluten food. The most favoured non-gluten product alternatives are the sponge cake. To produce a soft and elastic non-gluten sponge cake, then hydrocolloid is required. On the other side, the types and amounts of hydrocolloid are varied, depending on the product's types and ingredients. This research aims to determine the correct type and concentration of hydrocolloid (xanthan gum and guar gum) towards chemical quality and organoleptic of the non-gluten sponge cake from the best cowpea. This research would also help fulfil food availability and diversity for the increasing number of people with autism and celiac disease, reduce the consumption of wheat flour as the gluten source that is now still imported, and utilise and increase consumption of cowpea locally-sourced food. This research employs Randomised Block Design method consists of two factors: hydrocolloid type factor, which consists of two levels (xanthan gum and guar gum) and hydrocolloid concentration type factor, which consists of three levels (1 gr, 2 gr, and 3 gr). The chemical test parameters involve protein, water, and ash content. The organoleptic test parameters involve colour, aroma, flavour, and texture. This research resulted in the best treatment of the cowpea sponge cake is at the usage of xanthan gum type on the 2 grams concentration (HIK2) with the highest Result Value of 0.78, with research criteria scores as follows: flavour = 5.7 (like); texture = 5.6 (like); water content = 9.535%; protein content = 4.354%; colour = 5.4 (rather like); and ash content = 1.622%.